Toughening of low-weight foam-based composites - Erwin Merijn Wouterson (2010)
Various industries, incl. defense, aerospace and automotive, are spending large budgets on the development of lightweight materials. Especially, sandwich composites gain increasing attention due to their high strength-to-weight which allows for a structural weight reduction compared to conventional metallic structures. Sandwich composites comprise of fibrous outer layers and a core material. Syntactic foam, comprising of a binder and hollow microspheres, would be an attractive material to be used as the core material since it is a lightweight material with tremendous compressive strength, low moisture absorption, and low radar detectability. However, the major disadvantage of syntactic foam is its brittle behavior under mechanical loading. Due to its brittleness, it has a low resistance to the formation and propagation of cracks, limiting the number of advanced applications of syntactic foam.